2006
DOI: 10.1016/j.tics.2006.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Single-trial EEG–fMRI reveals the dynamics of cognitive function

Abstract: Two major non-invasive techniques in cognitive neuroscience, electroencephalography (EEG) and functional magnetic resonance imaging (fMRI), have complementary advantages with regard to their spatial and temporal resolution. Recent hardware and software developments have made it feasible to acquire EEG and fMRI data simultaneously. We emphasize the potential of simultaneous EEG and fMRI recordings to pursue new strategies in cognitive neuroimaging. Specifically, we propose that, by exploiting the combined spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
292
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(298 citation statements)
references
References 53 publications
4
292
0
2
Order By: Relevance
“…Although denoising and inclusion of parametric modulations into the stimulus paradigm (Eichele, et al, 2005), and temporal unmixing of the EEG (Debener, et al, 2005b) solve parts of the problem and make way for refined spatiotemporal mapping, there is still need for improvement of the analysis tools for integration of concurrent recordings (cf. Debener, et al, 2006). One such improvement is to unmix both modalities in parallel at the single-trial level, which follows naturally from the recent work (Calhoun, et al, 2006c;Debener, et al, 2005b;Eichele, et al, 2005) and the reasoning laid out above.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although denoising and inclusion of parametric modulations into the stimulus paradigm (Eichele, et al, 2005), and temporal unmixing of the EEG (Debener, et al, 2005b) solve parts of the problem and make way for refined spatiotemporal mapping, there is still need for improvement of the analysis tools for integration of concurrent recordings (cf. Debener, et al, 2006). One such improvement is to unmix both modalities in parallel at the single-trial level, which follows naturally from the recent work (Calhoun, et al, 2006c;Debener, et al, 2005b;Eichele, et al, 2005) and the reasoning laid out above.…”
Section: Introductionmentioning
confidence: 98%
“…These neuronal mass responses can be observed across scales and modalities from single unit recordings, intracranial and scalp electrophysiology, as well as metabolic and hemodynamic signals, but no single technique provides a sufficient view of the full temporal, spatial and functional extent of these responses. Visibility can be improved with techniques that integrate data across different neuroimaging modalities (Debener, et al, 2006;Hopfinger, et al, 2005;Horwitz, et al, 2002;Makeig, 2002). In the case of concurrent EEG-fMRI recordings, one can complement the temporal resolution provided by scalp potentials with the spatial precision of fMRI.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Makeig et al, 2002;Onton et al, 2005) have demonstrated that ICA can successfully be applied to EEG data to separate frontal theta activity from other (oscillatory) activity. Debener et al (2005Debener et al ( , 2006 demonstrated that ICA can be applied to EEG data measured in the MRI scanner to obtain single trial measures of evoked potentials that can be successfully correlated with the BOLD signal. Similarly, by correlating power fluctuations of the frontal theta components obtained by ICA with the BOLD signal in resting state, we hope to gain some insight into the neuronal structures that are associated with the frontal theta rhythm in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In statistical terms, we set the goal of assessing whether the experimental contrast ('go' vs. 'nogo')-to-noise ratio was greater in the ERPs acquired in the absence of concurrent MR gradient switching than in the ERPs acquired with concurrent gradient switching, both in averaged ERPs and over individual EEG segments. The latter analysis was motivated by the increasingly popular approach of correlating ERP component amplitude (or latency) with the fMRI signal over single trials (see Debener et al, 2006, for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, correlating the two measurements over single trials (e.g. Debener et al, 2005;Eichele et al, 2005;Bénar et al, 2007;Mantini et al, 2009;Warbrick et al, 2009) has been one of the primary motivations for combining EEG and fMRI acquisition (see Debener et al, 2006, andLaufs et al, 2008, for reviews).…”
Section: Introductionmentioning
confidence: 99%